The path to paradise: the inner world of suicide bombers and their dispatchers - Berḳo, ʿAnat (Praeger Security International, 2007)
Palestinian dispatcher of suicide bombers : "Find me, sad guys." -- The role of the dispatcher : "Everybody has his job, I dispatch the suicide bomber and he explodes." -- Organization : "The dispatchers don't send their own sons to blow themselves up" -- Dispatchers are held in high esteem : "I'm considered someone who does something good." -- Dispatcher macho : "My father taught it what it means to be a man and didn't allow us to be cowards." -- Sheikh Ahmad Yassin, Hamas founder : "The shaheed doesn't die, he lives with Allah." -- Women in prison : "She poured boiling margarine on my face." -- As Machiavelli said, "the end justifies the means." -- The book of mug shots : "Huda can't talk to you now, she's having her face done." -- The value of women : "I'll never do anyone any good, anyway." -- The terrorist's dream : "I've wanted to be a shaheeda ever since I was a little girl." -- Double standard : "Sure, I'd attack a kindergarten! I am able to look at your children and explode!" -- Is the "other" a human being? : "do Israeli mothers feel pain like we do?" -- A teenage shaheed : "My classmate enlisted me as a shaheed. He was paid and gave me 100 shekels." -- Paradise : "All that is forbidden in this world is allowed in paradise."